Fractionation and characterisation of dietary fibre from blackcurrant pomace. (August 2018) - Alba, K.; MacNaughtan, W.; Laws, A.P.; Foster, T.J.; Campbell, G.M.; Kontogiorgos, V.
Abstract: The potential of blackcurrant pomace as a raw material for the extraction of dietary fibre was evaluated using two pomaces one sourced from the UK and one from Poland. A fractionation protocol was designed to isolate and subsequently quantify the soluble and insoluble dietary fibre fractions. Blackcurrant pomace and isolated pectins, hemicelluloses and celluloses were assessed by means of sugar compositional analysis, spectroscopy, size exclusion chromatography and dilute solution viscometry. The blackcurrant pomaces presented considerable amounts of dietary fibre with soluble fibre ranging from 25 to 30% w/w and insoluble dietary fibre accounting for about 47% w/w for both pomaces. Blackcurrant pomaces differed in the amount of extracted pectins with an almost two times higher pectin yield obtained from blackcurrant pomace sourced from Poland. The hemicellulosic polysaccharide content was 15% w/w whereas the amount of cellulosic fraction varied from 14 to 17% w/w. Pectins isolated from both blackcurrant pomaces were LM pectins with a degree of esterification in the range of 11–38%. The work has identified that dietary fibres obtained from blackcurrant pomace had desirable ratio of insoluble to soluble fibre and are a potential new source of dietary fibre. Graphical abstract: Image 1 Highlights: Blackcurrant pomace is a new source of soluble and insoluble dietary fibres. Insoluble (∼47%) dietary fibres are found at higher levels than soluble (∼28%). The insoluble-to-soluble dietary fibre ratio of blackcurrant pomaces is 1.6–1.9 Minor differences observed between the two places of origin (UK, Poland).